Modelling the user education domain: a grounded theory approach - Caregnato, Sonia Elisa (2000)
This thesis reports a research work whose objective was to derive a grounded model of the user education domain, which was identified as pertaining to subject librarians' expertise, using a knowledge elicitation approach in the field of agricultural sciences. The knowledge elicitation framework adopted was that which sees knowledge acquisition as a process of modelling expertise, and the models derived as qualitative in nature. Accordingly, the main methodological approach involved was based on qualitative research and use of grounded theory methods. The research design was divided into three studies, all based on interview data. The research started by studying the role of subject librarians in academic libraries in the UK (Study One), which identified the area of user education for further study. Study Two proceeded to elicit information seeking practices and user education processes from academics and librarians. Finally, Study Three elicited information seeking practices of students who were engaged in library research. A model of the user education domain in the field of agricultural sciences in a Brazilian university was derived from the combination of the analysis of Study Two and Three. The model describes the library research process of individuals as happening in discipline specific contexts, influenced by the world at large. The process takes place through a series of information-seeking tasks and task-related strategies, which are employed to search external knowledge sources and satisfy an information need. During this interaction, internal knowledge sources are used and modified according to the tasks and strategies being carried out. If these internal knowledge sources are deficient for effective use of external knowledge sources, mediation strategies by an expert can help readjust the information-seeking process and alter the state of related internal knowledge sources The model proposed is used to derive recommendations for the design of user education programmes, subject librarians' work, and domain modelling using grounded theory.